The Impact of YouTube as an Interactive Social Studies Learning Platform for 7th Grade Students at Junior High School - Mawarni, Ersa Wahyu; Sulistyarini, Sulistyarini; Karolina, Venny; Ulfah, Maria; Barella, Yusawinur (research, training and philanthropy institution Natural Aceh, 2024)
This research regarding the use of YouTube learning media in ssocial studies subjects aims to determine its influence or impact on students as seen from the learning outcomes scores in class VII at SMP Negeri 1 Sungai Pinyuh. This research was conducted using a pre-experimental method with a one-group pretest-posttest design. The sample used comprises students from the class with the lowest average formative scores. The conclusive findings of the research suggest that using YouTube as an educational tool in the classroom positively impacts students' academic achievements. This is evident from the student's learning outcomes after the treatment, where most students showed significant improvement: 50% (N=16) reached the